Medial patellofemoral ligament reconstruction using autologous hamstring graft for recurrent patellar dislocation: a clinical and functional outcome evaluation - Ghosh, Sanjib; Das, Ayon; Baid, Mahak; Das, Arijit (International Journal of Research in Orthopaedics, 2021)
Patellofemoral instability is a painful and often recurring disorder with many negative long-term consequences. Surgical treatment for patellar dislocation has evolved from the initial medial reefing to the present-day anatomical reconstruction of medial patellofemoral ligament (MPFL) which is thought to be the most appropriate treatment. MPFL reconstruction successfully addresses patellofemoral instability by restoring the deficient most important static primary soft tissue restraint. This prospective case series was conducted at a Tertiary care Govt. Hospital in Kolkata between January 2019 to August 2020 on 15 patients who underwent MPFL reconstruction for recurrent patellar dislocation. All patients were followed up at an interval of 2 weeks, 6 weeks, 3 months and 6 months. Kujala score was used to assess the functional outcomes of the patients. Out of 15 patients, 13 (86.7%) showed good to excellent results whereas 2 (13.3%) had Fair outcome and none of the patients demonstrated Poor surgical result. The mean Kujala score improved from 49.6 pre-operatively to 92.7 post-operatively. By the end of 6 months follow-up, 13 (86.7%) patients achieved almost full range of motion. Majority (80%) of patients did not have any complications. Only 2 patients had a post-operative recurrence (13.3%). Reconstruction of MPFL using autologous hamstring graft showed excellent results over the short term with a low re-dislocation rate and acceptable complication rates. It greatly helps in preventing further episodes of patellar subluxations or dislocations and in improving quality of life.